2022
DOI: 10.3390/rs14133139
|View full text |Cite
|
Sign up to set email alerts
|

Can Satellite-Based Thermal Anomalies Be Indicative of Heatwaves? An Investigation for MODIS Land Surface Temperatures in the Mediterranean Region

Abstract: In recent years, an exceptional number of record-shattering temperature extremes have been observed, resulting in significant societal and environmental impacts. The Mediterranean region is particularly thermally vulnerable, frequently suffering from intense and severe heatwaves. Using daily temperature observations from 58 weather stations (NOAA Global Historical Climatology Network daily database) in the Mediterranean area, past heatwave episodes were initially detected. A daily LST time series was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 66 publications
5
16
0
Order By: Relevance
“…During the study period between 2002 and 2020, they noticed an increase in positive LST anomalies of 1.35 days/10 years during the daytime and 1.64 days/10 years during the nighttime, which was in line with the increase in heat wave days. Major events, such as the European heat wave in 2003, could be clearly detected from the number of LST anomaly days [19]. The global analysis of yearly maximum LST by Mildrexler et al [180] showed spatially continuous patches of positive LST anomalies over Europe in 2003 and Siberia in 2010, which corresponds to the reported heat waves.…”
Section: Atmospherementioning
confidence: 98%
See 4 more Smart Citations
“…During the study period between 2002 and 2020, they noticed an increase in positive LST anomalies of 1.35 days/10 years during the daytime and 1.64 days/10 years during the nighttime, which was in line with the increase in heat wave days. Major events, such as the European heat wave in 2003, could be clearly detected from the number of LST anomaly days [19]. The global analysis of yearly maximum LST by Mildrexler et al [180] showed spatially continuous patches of positive LST anomalies over Europe in 2003 and Siberia in 2010, which corresponds to the reported heat waves.…”
Section: Atmospherementioning
confidence: 98%
“…Heat wave metrics, therefore, are mostly based on positive LST or air temperature anomalies in the warm season. Agathangelidis et al [19] showed that, for the Mediterranean region, there is a high coincidence rate between heat wave days, detected with air temperature station measurements and LST anomalies. The match percentage was lower on the first days of the heat wave and increased as the heat wave evolved.…”
Section: Atmospherementioning
confidence: 99%
See 3 more Smart Citations